Biotope Protection Problems in Tervete Nature Park (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2006)
Tervete Nature Park is a particular cultural, historical and geographical object. To overcome problems with regard to the existing biotope protection, the inventory of woodland key habitats and natural meadows has been carried out using aprrobated research methods. Great biological diversity including great amount of medical and rare plants found in the Park has been described. Spridisu and Auziņu meadows are typical dry meadows. Silalibiesu, Illenu and Plavnieku meadows are moderately moistured meadows. Meadows' flora of Tervete Nature Park is formed by two vegetation classes: Molinio-Arrhenatheretea and Festuco-Brometea. A complex of measures has been offered to maintain biological diversity as will as for woodland biotopes and utilization of natural meadows.